Assisting Sharia banking financing programs in the development of MSMEs in Malang Regency - Mohammad Rizal; Muhammad Ridwan Basalamah; Arini Fitria Mustapita (Community Empowerment, 2021)
The MSMEs sector has a very important role in supporting the economy of Malang Regency. However, MSMEs have difficulty obtaining access to Islamic banking financing because of a few reasons: their management lacks a good financial administration system, business management is still manual and traditional, and most MSME owners are unable to separate the operational money for their households and businesses. These technical constraints make the owner think less about the goals or long-term strategic plans of his business. In Karangsuko Village, most of its population still rely on the MSMEs sector as a means of livelihood. This service aims to make MSMEs actors understand financial management, sharia accounts, financing rules from Islamic banks, preparation of financial reports, and drafting financing proposals to Islamic banks. This activity was implemented using the RRA (Rapid Rural Appraisal) method. With the systematic implementation of service activities by a team of lecturers at the Islamic University of Malang, the percentage of participants' understanding before and after the assistance was 18% and 87.20% respectively.